Ultrasound-Guided Tendon Fenestration - Chiavaras, Mary M.; Jacobson, Jon A. (Seminars in Musculoskeletal Radiology, 2013)
A potential treatment for chronic tendinosis or tendinopathy is percutaneous ultrasound-guided tendon fenestration, also termed dry needling or tenotomy. This procedure involves gently passing a needle through the abnormal tendon multiple times to change a chronic degenerative process into an acute condition that is more likely to heal. This article reviews the literature on tendon fenestration and describes the technical aspects of this procedure including postprocedural considerations. Although peer-reviewed literature on this topic is limited, studies to date have shown that ultrasound-guided tendon fenestration can improve patient symptoms. Several other percutaneous treatments for tendinopathy that include prolotherapy, autologous whole-blood injection, and autologous platelet-rich plasma injection are often performed in conjunction with fenestration. It is currently unknown if these other percutaneous procedures have any benefit over ultrasound-guided tendon fenestration alone.
Keywords: elbow; ultrasound; tendinosis; epicondylitis